Odpowiedzi

2010-04-15T16:37:01+02:00
2 1/2+x=4/-2,5
x=1,5

b.x-3,6=8/+3,6
x=11,6
c.-3 1/3-x=2/+3 1/3
x=5 1/3
d.2/5x=-4/:2/5
x=-10
e.x:4=-2,8/*4
x=-11,2
f.7,2-x=10,4/-7,2
x=3,2
2010-04-15T16:41:58+02:00
A) 2½ + x = 4
x = 4 - 2½
x = 1½

b)
x - 3,6 = 8
x = 8 + 3,6
x = 11,6

c)
3⅓ - x = 2
x = 2 - 3⅓
x = -1⅔

d)
⅖ × x = -4
⅖x = -4 | : ⅖
x = -10

e)
x : 4 = -2,8 | ×4
x = -11,2

f)

7,2 - x = 10,4
-x = 3,2 | : (-1)
x = -3,2



2010-04-15T16:44:22+02:00
A) 2 i1/2+x=4
5\2+x=4 /*2/5
x=8/5=1i1/3
b) x-3,6=8
x= 8+3,6
x=11,6
c) -3i1/3-x=2
-10/3-x=2 /*(-3/10)
-x=-6/10 /*(-1)
x=6/10=3/5
d) 2/5*x=-4 /*5/2
x=-4*5/2
x=-20/2=-10
e)x:4=-2,8 to to samo co x*1/4=-2,8 /*4
x=-2,8*4=-11,2
f) 7,2-x= 10,4
-x=10,4-7,2
-x=3,2 /*(-1)
x=-3,2